Mst1 Knockout Alleviates Mitochondrial Fission and Mitigates Left Ventricular Remodeling in the Development of Diabetic Cardiomyopathy - Feng, Xinyu; Wang, Shanjie; Yang, Xingjun; Lin, Jie; Man, Wanrong; Dong, Yuan; Zhang, Yan; Zhao, Zhijing; Wang, Haichang; Sun, Dongdong (Frontiers in Cell and Developmental Biology, 2021)
The disruption of mitochondrial dynamics is responsible for the development of diabetic cardiomyopathy (DCM). However, the mechanisms that regulate the balance of mitochondrial fission and fusion are not well understood. Wild-type, Mst1 transgenic and Mst1 knockout mice were induced with experimental diabetes by streptozotocin injection. In addition, primary neonatal cardiomyocytes were isolated and cultured to simulate diabetes to explore the mechanisms. Echocardiograms and hemodynamic measurements revealed that Mst1 knockout alleviated left ventricular remodeling and cardiac dysfunction in diabetic mice. Mst1 knockdown significantly decreased the number of TUNEL-positive cardiomyocytes subjected to high-glucose (HG) medium culture. Immunofluorescence study indicated that Mst1 overexpression enhanced, while Mst1 knockdown mitigated mitochondrial fission in DCM. Mst1 participated in the regulation of mitochondrial fission by upregulating the expression of Drp1, activating Drp1S616 phosphorylation and Drp1S637 dephosphorylation, as well as promoting Drp1 recruitment to the mitochondria. Furthermore, Drp1 knockdown abolished the effects of Mst1 on mitochondrial fission, mitochondrial membrane potential and mitochondrial dysfunction in cardiomyocytes subjected to HG treatment. These results indicated that Mst1 knockout inhibits mitochondrial fission and alleviates left ventricular remodeling thus prevents the development of DCM.